Context and social perceptions of blood donation in donors found positive for human immunodeficiency virus in France. Issue 9 (3rd July 2017) - Duquesnoy, Alice; Danic, Bruno; Santos, Aurélie; Martinaud, Christophe; Woimant, Geneviève; Laperche, Syria; Tiberghien, Pierre; Jauffret‐Roustide, Marie; Pillonel, Josiane; ,
Abstract : BACKGROUND: In France, information collected during postdonation interviews showed that a majority of human immunodeficiency virus (HIV)‐infected donors were not eligible to donate as per donor selection criteria. In the interest of blood safety, this study aimed to explore the mechanisms of noncompliance with blood donor selection criteria, notably the permanent deferral of men who have sex with men (MSM). STUDY DESIGN AND METHODS: Semistructured individual interviews were conducted with 32 blood donors found positive for HIV between mid‐2011 and 2014. Topics such as the experience and motivations for donating blood, understanding of selection criteria, sexual risk management, and opinions on donor selection were discussed. Transcripts were analyzed inductively. RESULTS: More than 50% of study participants were noncompliant with donor selection criteria. Reasons for nondisclosure of risk factors in the predonation questionnaire or the predonation interview included stigma, test‐seeking motivations, symbolic attachment to blood donation, and context of donation. Compliance to donor criteria was seen as secondary by donors who reaped personal benefits from the symbolism of their donation. Donors lacked self‐reflexivity in their assessment of risky sexual behavior. The "window period" and the underlying epidemiologic arguments for donor selection criteria were poorly understood. Nearly all participants disapproved of the permanent ban on blood donations from MSM. CONCLUSION: This study demonstrated the need for more communication on the epidemiologic basis for donor selection criteria and on the window period to facilitate donor compliance. These findings have already advanced improvements to predonation documents, in a larger context of 2016 donor selection criteria revision.